Externalized decondensed neutrophil chromatin occludes pancreatic ducts and drives pancreatitis - Leppkes, Moritz; Maueröder, Christian; Hirth, Sebastian; Nowecki, Stefanie; Günther, Claudia; Billmeier, Ulrike; Paulus, Susanne; Biermann, Mona; Munoz, Luis Enrique; Hoffmann, Markus; Wildner, Dane; Croxford, Andrew L.; et al. (Nature Communications, 2016)
Ductal occlusion has been postulated to precipitate focal pancreatic inflammation, while the nature of the primary occluding agents has remained elusive. Neutrophils make use of histone citrullination by peptidyl arginine deiminase-4 (PADI4) in contact to particulate agents to extrude decondensed chromatin as neutrophil extracellular traps (NETs). In high cellular density, NETs form macroscopically visible aggregates. Here we show that such aggregates form inside pancreatic ducts in humans and mice occluding pancreatic ducts and thereby driving pancreatic inflammation. Experimental models indicate that PADI4 is critical for intraductal aggregate formation and that PADI4-deficiency abrogates disease progression. Mechanistically, we identify the pancreatic juice as a strong instigator of neutrophil chromatin extrusion. Characteristic single components of pancreatic juice, such as bicarbonate ions and calcium carbonate crystals, induce aggregated NET formation. Ductal occlusion by aggregated NETs emerges as a pathomechanism with relevance in a plethora of inflammatory conditions involving secretory ducts.
EVALuna2:2052